Evaluating Inhibitory Effects of Paclitaxel and Vitamin D3 Loaded Poly Lactic Glycolic Acid Co-Delivery Nanoparticles on the Breast Cancer Cell Line - Sepideh Khodaverdi; Alireza Jafari; Farahnaz Movahedzadeh; Fateme Madani; Arshid Yousefi Avarvand; Siavash Falahatkar (Tabriz University of Medical Sciences, 2020)
Purpose: Paclitaxel (PTX) has transpired as a significant agent in the treatment of breast cancer. Meanwhile, polylactic glycolic acid (PLGA) nanoparticles (NPs) are able to increase the anticancer effect of the PTX in the blood. Methods: Nano-precipitation was used to prepare the PLGA-PTX-VitD3 co-delivery NPs. Drug loading, encapsulation efficiency, in vitro release profile, cell viability, migration, apoptosis, and bcl2 expression of NPs were evaluated. Results: The average size of co-delivery NPs was 231 ± 46 nm. Observed was a controlled release of the PTX and vitamin D3 from co-delivery NPs between 0.5 and 240 hours. MTT showed the ability of 8 μg.mL-1 of co-delivery NPs to kill 50 % of the MCF-7; likewise, the co-delivery NPs prevented MCF-7 migration. The co-delivery NPs led 46.35 % MCF-7 to enter primary apoptosis. 60.8% of MCF-7 in the control group were able to enter the G (1) phase of the cell cycle. The co-delivery NPs increased expression of bax. In addition to its higher toxicity against MCF-7 than that of PTX, co-delivery NPs were able to release drugs continuously for a long period, which indeed increased the efficiency of the drugs. Conclusion: The effect of co-delivery NPs on MCF-7 cell viability was different from that in other drugs. In fact, the co-deliver NPs were able to release drugs continuously for a long time, this could induce primary apoptosis in the MCF-7 and decrease the metastasis and toxicity of drugs.